Development of a Bayesian belief network for a boiling water reactor during fault conditions - Frid, Wiktor; Knochenhauer, Michael; Bednarski, Marcin (Computer Assisted Methods in Engineering and Science, 2022)
This paper describes briefly the development and verification of a probabilistic system for the rapid diagnosis of plant status and radioactive releases during postulated severe accidents in a Boiling Water Reactor nuclear power plant. The probabilistic approach uses Bayesian belief network methodology, and was developed in the STERPS project in the European Union 5-th Euroatom Framework program.